Arguments for Recognizing the Future as Non-Probabilistic: Considerations in the Framework of a Hypothesized Precognition Theory - Dahmen, Thorsten (Journal of Scientific Exploration, 2025)
The debate on whether the future is predetermined (fixed) or probabilistic (uncertain) dates back to ancient times but is still ongoing. An essential basis in this paper is the view that a conclusive answer can neither be drawn exclusively from physics nor additionally from philosophical modes of argumentation. It is considered necessary to take a transtemporal process of cognition, which is in parapsychology termed precognition, into account. This brings in the new aspect that predictability no longer needs to be synonymous with computability and the analytic describability of causal event chains, which also has an impact on the meaning of the terms that are used. Furthermore, this allows a superior timeless perspective that invalidates the logic from the present-time perspective and extends the concept of observability and reality. Since both subjects are interrelated and cannot be considered independently of each other, a psychophysical hypothesis about how precognition interacts with the future is an integral part of this proposal, its experimental verification is described. This encompasses explanations of how logical paradoxes, which are often attributed to precognition, do not exist and how intelligible information can be consistently shared between the present and the future in four-dimensional spacetime. The argumentation for a non-probabilistic, fixed future comprises the physical point of view, referencing special relativity theory and quantum theory, but considers the nonphysical aspects of the mind with the same matter-of-factness. A similar conclusion that the future is deterministic is not asserted since this term combines causality and predictability in an inscrutable way by making complex assumptions that are not precisely and uniformly defined. A closer description of the problem reveals that the frequently used keywords “deterministic” and “probabilistic” lose their usual meaning if the frame of reference given here is acknowledged. Therefore, many reservations that consider only a probabilistic future as reasonable might be unnecessary.